PENGUKURAN JEJAK KARBON DAN INSENTIF FINANSIAL DALAM RANTAI PASOKAN EMPIRIS - Riduan Siagian; Adrian K. Tarigan; Josua Tahan Jaya Sitorus (Jurnal Industri Kreatif dan Inovatif, 2025)
This study empirically examines carbon footprint measurement within supply chain management and the role of financial incentives in driving emission reductions. Since supply chains may contribute up to 90% of a company’s emissions and indirect emissions (Scope 3) can be as much as 26 times higher than operational emissions, the study highlights key challenges including incomplete supplier emission data, variability in measurement methodologies, and adoption barriers for enabling technologies. It also analyzes the effectiveness of sustainable funding models—such as Sustainable Supply Chain Finance (SSCF), sustainability-linked loans (SLL), and green bonds—as well as internal incentive mechanisms cost-sharing (CS) and preferential financing (PF). The findings indicate that well-designed financial incentives can increase the likelihood that suppliers reduce emissions by up to 52%. The study further proposes the use of innovative technologies, including blockchain and the Internet of Things (IoT), to improve the accuracy, transparency, and real-time verification of emissions data. Overall, the research concludes that integrating robust measurement systems with performance-based incentives is a crucial strategy for companies to enhance emissions management and supply chain sustainability.